Pengembangan Kompetensi Guru melalui Sosialisasi dan Workshop Model Pembelajaran RADEC Berorientasi Multiliterasi - Wahyu Sopandi; Muh Erwinto Imran; Hany Handayani; Chaerun Anwar (Universitas Mathla'ul Anwar Banten, 2020)
TEACHER COMPETENCY DEVELOPMENT THROUGH SOCIALIZATION AND MULTILITERATION ORIENTED RADEC LEARNING MODEL WORKSHOP. This study was conducted on teachers in Ciamis Regency, which examined the attitudes, knowledge and skills of teachers as well as how the teacher competency training needs. Implementation of teacher competency training which is conducted to facilitate teachers in planning, implementing and evaluating multiliterative oriented learning. The teacher competency development workshop was attended by 70 teachers from various elementary schools in Ciamis district. In the workshop activities, various learning issues were explained in the era 4.0 and society 5.0 and learning models that can facilitate various 21st century skills including multiliterative learning. The teacher competency development workshop can support them to overcome the challenges they face during their teaching practice. The data shows that there is a very high need for training that can assist teachers in mastering various teaching skills, especially in facilitating multiliteracy-oriented learning. Some data also show about the teacher's lack of understanding of the learning model. There are also data results that show a lack of student involvement in multiteracy activities both in learning and given assignments. This is reinforced by the low percentage of teaching activities that involve students in higher order thinking skills.